Financial Literacy and Attitudes Predict Microenterprise Monetary Management Practices in Boyolali: Literasi dan Sikap Keuangan Memprediksi Praktik Pengelolaan Moneter UMKM di Boyolali - Ananda Mey Rizki Sholikhah; Aris Edi Sarwono; Sinta Putriana (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Small-scale enterprises serve as primary pillars of the national economy by significantly contributing to the gross domestic product and employment. Specific Background Despite their strategic economic position, many business owners demonstrate inadequate monetary practices, specifically regarding unrecorded transactions and poor cash flow regulation. Knowledge Gap Previous empirical studies examining the relationships between economic knowledge, psychological tendencies, and administrative practices present inconsistent and contradictory findings. Aims This study analyzes how financial literacy and financial attitudes determine the financial management behavior of enterprise owners within the Boyolali region. Results Utilizing a quantitative survey methodology with multiple linear regression on 100 purposively sampled respondents, the findings demonstrate that both financial literacy and financial attitudes positively and significantly direct operational decisions. Financial literacy emerges as the dominant factor, and together with financial attitudes, explains half of the behavioral variance. Novelty This research validates the Theory of Planned Behavior within a uniquely mixed urban and rural socio-economic demographic, providing context-specific empirical evidence that resolves prior academic inconsistencies. Implications Regional governments and institutions must implement continuous educational and mentoring programs to cultivate positive psychological tendencies and ensure sustainable business operations. Highlights Economic knowledge acts as the dominant determinant for daily business decisions. Psychological tendencies positively direct the resource planning of small-scale entrepreneurs. Continuous governmental mentoring programs secure the sustainability of local commercial operations. Keywords Economic Knowledge; Psychological Tendencies; Resource Planning; Small-Scale Entrepreneurs; Sustainable Operations